Effects of a Concurrent Mixed-Modality (Telerehabilitation and Face-to-Face) Exercise Rehabilitation Program in a Patient with Multiple Myeloma Prior to Spinal Cord Transplantation: A Case Study - Juan Carlos Hernández-Sigüenza; Paula Blanco-Gimenez; Luis Baraja-Vegas; Josep López-Soler; Francisco Javier Falaguera-Vera; Eloy Jaenada-Carrilero; Juan Vicente-Mampel (Current Oncology)
Introduction: Multiple myeloma constitutes approximately 12% of hematologic malignancies and predominantly affects older adults, significantly compromising their quality of life. Although exercise interventions have shown benefits in oncology, evidence specific to MM remains limited and of low certainty. The presence of complex comorbidities in MM patients necessitates highly individualized approaches. Prehabilitation has emerged as a promising strategy to enhance functional capacity prior to autologous stem cell transplantation. This case study evaluates the feasibility of a personalized, scheduled exercise intervention delivered via telerehabilitation. Intervention: This case study seeks to examine the feasibility of implementing a personalized and scheduled exercise intervention within a telerehabilitation framework for a medically complex patient with multiple myeloma (MM). The 12-week prehabilitation protocol is designed to enhance physical function prior to autologous bone marrow transplantation by integrating therapeutic exercise targeting key parameters related to quality of life and clinical resilience, such as muscular strength, aerobic capacity, coordination, and overall well-being. The intervention includes concurrent training (strength and aerobic exercises) delivered 2–3 times per week, with aerobic activities conducted independently at home through a virtual format. Assessments were performed at baseline and post-intervention. Results and conclusion: A personalized exercise program, implemented through a hybrid model of in-person and telerehabilitation, is both feasible and safe. It has the potential to enhance physical function and quality of life in patients with multiple myeloma. Further research is necessary to validate these findings across broader patient populations.